Mobilidade acadêmica internacional, razões da baixa mobilidade dos estudantes de colleges do Reino Unido - Bragato, Cintia Nunes (2015)
In an increasingly globalized world, the internationalization of the higher education obtains a great and big importance. The international academic mobility, as part of this process, has moved more and more students beyond their home countries and in this context, as in migration processes, we observe significant differences between the regions that "export" and "import" more students. United Kingdom appears as one of the world leaders in receiving international students; however has low mobility of students beyond its borders. Trying to understand better this phenomenon, the research focused on the reasons why British students of colleges have low interest in academic mobility programs. The approach chosen for this research was empirical quantitative and the method used was the survey that is intended to produce descriptions and quantitative analysis on aspects of a specific population. As a result, it was observed that the lack of the financial resources, lack of knowledge of a second language, family issues and the absence of having the life experience in another culture are factors that directly affect the decision of the British students not to invest in international academic mobility programs.